Managerial Resourcefulness in School Administrators: Association with Stress and Depression - Turhan, Muhammed; Karabatak, Songul; Sengur, Donus; Zincirli, Muhammed (Cukurova Univ, 2018)
The purpose of this study was to determine the relationship between school administrators' levels of managerial resourcefulness and the levels of stress and depression they experience. For this reason, a relational research model was used throughout the study. The study sample consisted of 704 school administrators who served in Elazig city center and its districts. Data was collected from 205 school administrators using the method of disproportionate stratified sampling. The Managerial Resourcefulness Scale, Stress Scale, and Depression Scale were used to collect the data. According to the findings, the level of managerial resourcefulness has a high impact on the experience of stress and depression. When managerial resourcefulness increased, the level of stress and depression decreased. When the significance levels of the regression coefficients were examined, the variables of cautiousness and decisiveness were discovered to be significant predictors of both depression and stress scores.
Keywords: Managerial resourcefulness; Stress; Depression; School administrator